a)
p_initial = m • v + m' • 0
p_initial = m • v
p_final = (m + m') • v_final
p_initial = p_final
m • v = (m + m') • v_final
20 g • 10 cm/s = (20 g + 10 g) • v_final
200 g•cm/s = 30 g • v_final
v_final = 200 g•cm/s : 30 g
v_final = 6.67 cm/s
b)
E_initial = 0.5 • m • v^2 + 0.5 • m' • 0^2
E_initial = 0.5 • m • v^2
E_final = 0.5 • (m + m') • v_final^2
E_pierduta = E_initial - E_final
E_pierduta = 0.5 • m • v^2 - 0.5 • (m + m') • v_final^2
E_pierduta = 0.5 • 20 g • (10 cm/s)^2 - 0.5 • 30 g • (6.67 cm/s)^2
E_pierduta = 1000 g•cm^2/s^2 - 1000 g*cm^2/s^2
E_pierduta = 0